2012
DOI: 10.1111/j.1442-9071.2012.02770.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Structure–function relationship’ in glaucoma: past thinking and current concepts

Abstract: An understanding of the relationship between functional and structural measures in primary open angle glaucoma (POAG) is necessary for both grading the severity of disease and for understanding the natural history of the condition. This article outlines the current evidence for the nature of this relationship, and highlights the current mathematical models linking structure and function. Large clinical trials demonstrate that both structural and functional change are apparent in advanced stages of disease, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
172
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(178 citation statements)
references
References 90 publications
4
172
0
2
Order By: Relevance
“…Garway-Heath demonstrated that the appearance of a functional reserve could be explained as a statistical artifact using log units for perimetric sensitivity and linear units for anatomical measurements [2]. Even now, a structure-function relationship remains controversial in the earliest stages of ''preperimetric'' glaucoma [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Garway-Heath demonstrated that the appearance of a functional reserve could be explained as a statistical artifact using log units for perimetric sensitivity and linear units for anatomical measurements [2]. Even now, a structure-function relationship remains controversial in the earliest stages of ''preperimetric'' glaucoma [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Advances in imaging technology now readily available to the clinic, like optical coherence tomography, infer the feasibility of objectively measuring structural progression in glaucoma. Yet the research community still struggles with the link between these structural assessments and how they impact on visual function; an excellent recent review is given by Malik et al 13 I suggest the most important measure for disease progression in glaucoma is the functionally relevant assessment of the visual field; it certainly ought to be a key determinant in assessing effectiveness of treatments in a clinical trial setting. Unfortunately, effective visual field assessment can be difficult and identifying changes in follow-up (progression) beyond the measurement variability is a well-known thorny issue.…”
Section: The Burden Of Glaucomamentioning
confidence: 99%
“…Dynamic models have been developed for other chronic diseases [12,13] and this approach could be applied to glaucoma progression. Recent efforts in 3 this direction have been made and deserve attention. Schell et al [14] proposed a dynamic model to personalize the frequency of clinic visits for glaucoma patients based on each patient's historical intraocular pressure levels and their performance on visual field tests.…”
mentioning
confidence: 99%
“…Determining how structural and functional data should be combined, however, is complicated by the fact that the relationship between structure and function is not well understood in glaucoma [3]. For example, while some studies suggested that structure and function were best defined by a curvilinear relationship [4][5][6], recent studies have demonstrated that the structure-function relationship may be linear when both measurements are expressed in linear units [7][8][9][10][11].…”
mentioning
confidence: 99%